Pengaruh Latihan Ladder Drill Terhadap Peningkatan Kecepatan Lari dan Daya Tahan Kardiovaskular pada Pemain Sepak Bola SMPN 20 Surabaya - Fadhilah Nanda Kusuma; Roy Januardi Irawan; Dita Yuliastrid; Mokh. Nur Bawono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of ladder drill training on improving speed and endurance in junior high school football players. The research used an experimental design with a one-group pre-test and post-test approach. Thirty two male players participated as subjects and underwent a six-week ladder drill training program, conducted three times per week. Data on speed were collected using a 20-meter sprint test, while endurance was assessed using the bleep test. The Shapiro–Wilk test was applied to verify data normality, and since the data did not meet the normality assumption, the Wilcoxon Signed Rank Test was used for inferential analysis. The results showed a significant improvement in both sprint performance and endurance levels (p < 0.05), indicating that ladder drill training effectively enhances neuromuscular coordination and cardiovascular endurance simultaneously. In conclusion, that ladder drills, as a form of agility-based exercise, can serve as a practical and efficient conditioning method for developing fundamental physical abilities in young football players. Keywords: Endurance, Speed, Ladder Drill, Football